Genomic variants association with selective hypersensitivityreactions to amoxicillin and clavulanic acid - Nuñez, Rafael; Fernández-Santamaría, Rubén; Salas, María; Bogas, Gador; Diez-Echave, Patricia; Mayorga Mayorga, Cristobalina; Torres-Jaén, María Josefa; Fernández-Duarte, Tahía Diana (Wiley, 2024)
In summary, there are rare variants found in our patients that could be related to the development of AX or CLV- induced IDHRs. Interestingly, some of these rare variants could be associated with selective response to AX, such as the proapoptotic endonuclease ENDOG and neutrophil degranulation pathway, previously associ- ated with drug- induced anaphylaxis,6 or to CLV, like immunoprote- asome component PSMD8. Differences could be related to nature and metabolic characteristics of each drug; however, more research is needed. These findings represent a first step to identify potential genetic biomarkers to predict the susceptibility of suffering AX and CLV IDHRs.
Keywords: Alergia; Genomic variants; Hypersensitivity reactions; Amoxicillin; Clavulanic acid